Evolution of Outbreaks, Lessons Learnt and Challenges Towards âNew NormalcyââPost COVID-19 World - Vaithilingam, C.A. (Springer Science and Business Media Deutschland GmbH, 2022)
A new era in epidemics started due to unhealthy practices, population density, environmental changes, migration and deforestation. The rapidity in the spread is primarily due to globalization as we moved to the industrial revolution where everything is internet-connected. In past 30Â years, the trend exhibits an increase in the number of epidemics challenging the social well-being, the economy and to some extent the national security. And this translates to the impact on the industrial growth, the race of future together fighting with the newest of the viruses. This paper analyzes and reviews the outbreaks from the start of the revolutionary steam power generation to the modern days, their impact to generate new values to the society that translated the newer solutions to become new norms. Impact on the outbreaks on the various key sectors and the measures that lead us to overcome is presented. We present the new normal which would become normal in the near future, the post COVID-19 scenario. Â© 2022, Institute of Technology PETRONAS Sdn Bhd.